Using effective signal filtering methods to data processing from a fiber-optic temperature sensor - I. A. Ershov (Омский научный вестник)
The article deals with signal processing of a fiber-optic temperature sensor using extremal filtering and filtering with Wavelet transforms. The aim of this work is to find a way to reduce the response time in a fiber-optic temperature sensor by using effective signal processing methods. Reducing the response time of systems for monitoring hazardous production facilities is rarely discussed in the literature. The results showed that the use of extreme filtering and filtering with Wavelet transforms can significantly reduce the number of implementations necessary to identify a signal with a low signal-to-noise ratio.